TECHNIQUE FOR DETERMINATION OF SURFACE FRACTAL DIMENSION AND MORPHOLOGY OF MESOPOROUS TITANIA USING DYNAMIC FLOW ADSORPTION AND ITS CHARACTERIZATION - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
ABSTRACT Received September 17, 2008